Die Historische Geographie in Deutschland nach 1945 - Fehn, Klaus (ERDKUNDE, 1982)
The first part of the contribution briefly presents the situation of historical geography in Germany after 1945, with special reference to those topics which the following papers did not touch upon - or did so only in passing. These are chiefly the beginnings of theoretical historical geography and the work of German historical geographers abroad. The second part formulates questions and lists some aspects for future discussion. The main questions are as follows: 1. Why should geography consider the historical dimension? 2. What is the object of historical-geographical research? 3. What sort of research approaches is historical geography to use? 4. What are the consequences of depending upon historical sources for historical geography? 5. Can and ought historical geography to contribute to spatial planning? 6. What type of scientific organisation is historical geography to strive for? 7. How is historical geography to be firmly established in university course structures? 8. How is historical geography to be taught in schools?